Human serum albumin (HSA) regulates the expression of histone-like nucleoid structure protein (H-NS) in Acinetobacter baumannii - Escalante, Jenny (2022)
Fil: Fil: Escalante, Jenny. California State University Fullerton. College of Natural Sciences and Mathematics. Department of Biological Science. Center for Applied Biotechnology Studies; United States.